Letter from Tennis Harrold and Lawrence Boyer to Jane Tolmach - Tennis Harrold::::::; Lawrence A. Boyer:::::: (1970)
A letter from Tennis Harrold and Lawrence A. Boyer to Jane Tolmach congratulating her on her election onto the Oxnard City Council.